A questão da metáfora, da referência e do sentido em pesquisas qualitativas: o aporte da sociopoética - Jacques Gauthier Zanidê (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
Considers the question of the production of heterogeneous meanings by the subjects and by the researcher in qualitative investigations. In reference to Deleuze and Guattaris concept of collective stating arrangement and its four components, the article focuses its attention on the question of the metaphor, its meaning and the interreferential world that it creates in common language and in the process of research. It reveals that with reference to Ricoeurs studies and Peirces semiotics, and based on recent research in the domain of popular education, socio-poetics -an innovative method of research, which uses artistic techniques for the production of data and trusts in the whole body as a source of knowledge - articulates affects with concepts, and promotes different kinds of abduction or intuition. This promotes the creation of confects, intermediaries between concepts and affects, as well as the creation of philosophical concepts by the researcher-group, subject and collective author of the research.